Efficacy and Safety of a Combination of Enteral and Parenteral Nutrition Support in the Postoperative Period for Patients with Gastrointestinal Cancer: A Systematic Review and Meta-Analysis - Meixiang Cai; Bo Yang; Yaping Zheng; Lei Ding (Balkan Medical Journal)
Background: Postoperative nutritional support in gastrointestinal cancer, including enteral nutrition (EN), parenteral nutrition (PN), and combined nutrition strategies, is vital for enhancing recovery and patient outcomes. Aims: We aimed to comprehensively evaluate the impact of postoperative EN, PN, and EN + PN in patients with gastrointestinal cancer. Methods: PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wan Fang, and VIP were searched from conception until January 2, 2024. Randomized controlled trials (RCTs) that compared different postoperative nutritional support (EN, PN, or EN + PN) in patients with gastrointestinal cancer were included. The Cochrane Risk of Bias Assessment tool was used to assess the quality of the RCTs. Fixed- and random-effects models were chosen according to the heterogeneity of variables for the synthesis of results. Continuous and categorical variables were analyzed using the weighted mean difference or relative risk (RR) and 95% confidence interval (CI). Results: In this meta-analysis, 11 RCTs were included. The PN + EN group exhibited significantly improved postoperative recovery, nutritional function, and immune indicators than the PN and EN groups (p < 0.05). Additionally, a higher incidence of postoperative complications such as abdominal distension (RR: 2.53; 95% CI: 1.17-5.49), nausea/vomiting (RR: 2.01; 95% CI: 1.09-3.71), and diarrhea (RR: 3.17; 95% CI: 1.41-7.10) was observed in the EN group than in the PN + EN group. Conclusion: Combining supplemental PN with enteral support improves energy intake and prognosis in gastrointestinal cancer, though limited studies restrict publication bias evaluation.